CYBERTERRORISM - WHEN TECHNOLOGY BECAME A WEAPON - Kontselidze, Achiko (European Scientific Journal, ESJ, 2015)
Everyone is well aware that the technological revolution of the 21st century is considered to be the time when the highest level was reached by the magnitude of computerization. If we look at the process of computerization, we can have the feeling that soon there will be no need for the phenomenon of human society, "everyone" and ’’would" be replaced by a computer. It is impossible not to note the positive changes that computerization has brought to mankind. Nowadays, e-mail can do it in one big case that a group of people spent months. It can be said that "streamlined" Modern Human Life. Every day a person can take an unlimited amount of information through a computer which makes it a much more rational and progressive thinking makes. Entering a useful discussion of the results will take us far; the author has set a goal to review the work of the negative aspects of the phenomenon of cyberspace. At the present stage of human development, when properly prepared, include the creation of a virtual network to create a global base, the human consciousness of the real world to the virtual society. And a broad range of the protected person “solves" the virtual world, as well as by the nature of the crime and the transfer of real transformation from the virtual world, where the offender and the offense has faced more solid leverage to protect oneself. Noone disputes the matter, the present reality is so increased offender "knowledge" that is difficult to fight against crime, the virtual world, around the processes being developed so rapidly that the virtual world of the crime committed against one of the two is difficult. In this study, the author aims to review the virtual cyber crime is one of the most severe form (phenomenon) – cyber terrorism, which in many cases involves a much wider range of recipients, and in many cases the effect is much more "devastating" than the force of an ordinary computer crime. Due to increased danger of cyber terrorism has long been a subject of debate has become the leading national governments.